An improved flying restart method of sensorless PMSM drive systems fed by an ANPC inverter using repetitive zero voltage vectors - Seo, Dong Woo; Bak, Yeongsu; Cho, Sungjoon; Bae, Kyuchul; Lee, Kyo Beum (Conference Proceedings - IEEE Applied Power Electronics Conference and Exposition - APEC, 2019)
This paper presents an improved flying restart method of sensorless permanent-magnet synchronous motor (PMSM) drive system fed by an active neutral-point clamped (ANPC) inverter using repetitive zero voltage vectors. In order to restart the sensorless PMSM drive system, the estimation method for initial rotor position and speed is necessary due to the absence of sensor. The initial rotor position and speed can be estimated by using current vector generated after applying zero voltage vector by the ANPC inverter with the rotating PMSM. However, when the flying restart method is implemented for the industrial PMSM drive system, there are many difficulties to measure accurate current vector due to harmonic components and electromagnetic interference (EMI) by switching operation. Therefore, in this paper, the improved flying restart method using repetitive zero voltage vectors is proposed in order to implement a reliable operation of the sensorless PMSM drive system fed by the ANPC inverter. The effectiveness of the proposed method is verified by simulation and experimental results.
Keywords: Active neutral point clamped; Active npc; Flying restart; Initial rotor position; PMSM drives; Sensorless permanent magnet synchronous motor; Switching operations; Voltage vectors; Active NPC; Flying restart; PMSM drive system; Repetitive voltage vectors; Sensorless control